‘Great Stuff!’ - Müller, Eggo (VIEW Journal of European Television History and Culture, 2018)
In 2014, British Pathé launched its YouTube channel with more than 85,000 items of audiovisual heritage from the 20th century. This article analyses the curational strategies of this channel as developed by the German multi-channel network Mediakraft in consideration of YouTube’s algorithms and supposed user expectations. This article argues that, in the context of YouTube’s commercial ecosystem, Mediakraft’s curation emphasizes celebrities, spectacular historical events, and curiosities to attract users online.